Load management in tendinopathy: Clinical progression for Achilles and patellar tendinopathy - Mascaró, A.; Cos, M. A.; Morral, A.; Roig, A.; Purdam, C.; Cook, J. (Apunts Medicina de l'Esport, 2018)
Achilles and patellar tendons are commonly affected by tendinopathy. Injury to these tendons can severely impact upon sports, recreational and everyday activities. Eccentric musculotendinous loading has become the dominant conservative intervention strategy for Achilles and patellar tendinopathy over the last two decades. Eccentric loading involves isolated, slow lengthening muscle contractions. Systematic reviews have evaluated the evidence for eccentric muscle loading in Achilles and patellar tendinopathy, concluding that outcomes are promising but high-quality evidence is lacking. Eccentric loading may not be effective for all patients (athletes and non-athletes) affected by tendinopathy. It is possible that in athletes, eccentric work is an inadequate load on the muscle and tendon. A rehabilitation program aiming to increase tendon load tolerance must obviously include strength exercises, but should also add speed and energy storage and release. The aim of this paper is to document a rehabilitation protocol for Achilles and patellar tendinopathy. It consists of simple and pragmatic exercises designed to incorporate progressive load to the tendon: isometric work, strength, functional strength, speed and jumping exercises to adapt the tendon to the ability to store and release energy. This article would be the first step for an upcoming multicentre randomized controlled trial to investigate its efficacy. Abstract from author